Reconceptualising the Elements of Islamic Propagation: Religious Response and Adaptation to New Media - Adeni, Adeni; Bakti, Andi Faisal (Jurnal Komunikasi Islam, 2020)
This paper aims to examine the fundamental concepts of da'wah in response to new media culture. Using a qualitative research for conceptual design, this study has found that the proliferation of cyber religious proselytizing leads the elements of da'wah have become ever-widening concepts. The concept of da’i, for instance, has experienced the reconceptualisation that not only refers to person who conveys Islamic teachings through religious sermon (khutbah), but also denotes to a creative content provider for da’wah purposes in the internet. Additionally, the power of preaching in the new media lies in the quality of message, that is, good, comprehensive and argumentative. Similarly, redefinition of the concepts ma'du, feedback, and other da'wah elements occur as response to digital media culture.